Strategi Pemerintah Dalam Penanggulangan Covid-19 Pada Sekretariat Satuan Tugas Penanganan Covid-19 Kota Makassar - Faradillah, Andi; Abdi, Abdi; Nasrulhaq, Nasrulhaq (Universitas Muhammadiyah Makassar, 2021)
ABSTRACTThis study purposed to find out the government's strategy in dealing with Covid-19 at the Makassar City Covid-19 Task Force Secretariat. This study used descriptive qualitative . The data sources in this study were primary data sources and secondary data sources with the number of informants as many as 8 people. Data collection techniques using the method of observation, interviews and documentation. The results of this study were 1) the organizational strategy in dealing with Covid-19 in the Makassar city covid-19 handling task force that the vision and mission of the covid-19 handling unit were not stated. 2) The program strategy in dealing with COVID-19 in the Makassar City Covid-19 handling task force had been carried out to the maximum, seen from the linkage between the program and the tasks assigned. 3) The strategy to support resources in dealing with Covid-19 required a budget called Unexpected Costs (BTT) obtained from the APBD. 4) In the institutional strategy, several strategies were taken by the government in accelerating the handling of Covid-19, namely the first strategy, which was an increase in 3 M, namely wearing masks, washing hands, maintaining distance. Keywords: Strategy, Government, Covid-19 Response